THE 'INCA' PROM THE ROYAL COMMENTS: DESCRIPTION OFFICfiONALACfANT - Coello, Oscar (2010)
The following arricle describes the fictional speaker from Roy;d comments as long asrhe fe<tture from a lirerary narrative which may be atrached to the gcnre of rhc novel',.;hisrory. It is a shallow <lnrtly.sis of the sender which uses sotne tools tfom rhe dassicsemiotics. Article produced as a tribute to rhe fourth centenary of the pie ce.